Hubungan Health Literacy dengan Kepatuhan Minum Obat pada Pasien Hipertensi di Puskesmas Simpang IV Sipin - Ariani, Dhea; Rudini, Dini; Sari, Yulia Indah Permata; Martawinarti, Rts Netisa; Sari, Putri Irwanti (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Hypertension is classified as a non-communicable disease that necessitates prolonged therapeutic management. Adherence to antihypertensive medication is a key determinant in achieving controlled blood pressure levels and preventing potential complications. Health literacy likewise plays a critical role in shaping an individual’s capacity to comprehend medical information and make informed decisions related to treatment. This study was conducted to examine the association between health literacy and medication adherence among individuals with hypertension in the operational area of Puskesmas Simpang IV Sipin. This research employed a quantitative approach with a cross-sectional design. A total of 150 participants were recruited using a purposive sampling technique. Data collection utilized the HLS-EU-Q16 and MMAS-8 instruments, while data analysis was performed using Pearson correlation. The findings revealed that the average health literacy score was 10.61, and the average medication adherence score was 5.86. Pearson correlation testing showed a significant relationship between health literacy and medication adherence (p < 0.001) with a correlation coefficient (r = 0.65). These results indicate that higher levels of health literacy are associated with better adherence to antihypertensive therapy. Enhancing patients’ health literacy may therefore serve as an effective strategy to improve adherence to antihypertensive treatment.